METHODOLOGICAL BASIS FOR CREATION OF ECONOMIC UNIONS - Evgeny Georgiyevich Anisimov; Tatyana Nikolayevna Saurenko (Advanced Engineering Research)
A general methodological approach to the management of the creation and development of economic associations is considered. It is based on their representation in the form of a focused and evolving process whose driving force is the dialectical unity and struggle between the need and the opportunity, between the conceptual and constructive layouts of the association. Structurally, the process is presented in the form of a directed graph integrating its steps and sub-steps. Consistent implementation of the tasks of these steps ensures the generation of justified decisions on the creation and development of economic associations. The complexity and diversity of these problems calls for their formalization. At that, a key formalization element is a formal representation of the comparative evaluation procedure for the options of the state associations. The comparative evaluation methodology for the variants of their unification is described through the formal apparatus of the theory of sets.